2020
DOI: 10.1007/s10853-020-05326-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of weld seam surface and corrosion behavior of laser-beam-welded AISI 2205 duplex stainless steel in simulated body fluid

Abstract: In this study, AISI 2205 duplex stainless steel was joined with laser welding. Base material and laser-welded samples were kept in simulated body fluid (SBF) for 1, 3, 7, 14, 21, and 28 days. This research investigated microstructure, hydroxyapatite (HA) structure formed on surfaces, surface topography, and corrosion properties of samples which were kept in SBF. Characterization studies were performed by using microhardness, optical microscope, macroscope, SEM-EDS, XRD, and atomic force microscope. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The corrosion behavior of the welded joint of pipeline steel may be different from that of the base metal, especially the welding residual stress closely related to the welding process. Therefore, the earliest work in this area was research on welding residual stress, mainly studying postweld heat treatment and adjusting the welding process, so as to reduce welding residual stress and improve the corrosion resistance of the welded structure (Kse, 2020). After determining the corrosion system and corrosion environment of the base metal, the alloy composition and the content of the welding material are important factors that determine the composition, structure, and performance of the weld.…”
Section: Discussionmentioning
confidence: 99%
“…The corrosion behavior of the welded joint of pipeline steel may be different from that of the base metal, especially the welding residual stress closely related to the welding process. Therefore, the earliest work in this area was research on welding residual stress, mainly studying postweld heat treatment and adjusting the welding process, so as to reduce welding residual stress and improve the corrosion resistance of the welded structure (Kse, 2020). After determining the corrosion system and corrosion environment of the base metal, the alloy composition and the content of the welding material are important factors that determine the composition, structure, and performance of the weld.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the investigation of DSS corrosion resistance (2205 alloy) in as built condition [31,32], many experimental studies focused on coating the biomaterial by the electrophoretic deposition of a hydroxyapatite/titania nanocomposite [16] and by electrical discharge [15] to enhance the DSS biological response and corrosion resistance. Kose et al [31] investigated the corrosion resistance and apatite formation on the surface of base and laser-welded AISI 2205 DSS implants in SBF for 1, 3, 7, 14, 21, and 28 days. The samples were laser-welded using the following values of laser power [W] and scanning speed [cm/min]: C1-3500 W, 90 cm/min; C2-3500 W, 270 cm/min; C3-4000 W, 90 cm/min, and C4-4000 W, 180 cm/min.…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…Figure 8 shows the potentiodynamic polarization curves of samples with different Y 2 O 3 addition amounts in NaCl solution with mass fraction of 3.5wt%. Thin chromium-oxide film is easily formed on the surface of 316 L austenitic stainless steel [29], which is present as a passivated zone in Figure 8. Previous studies have indicated the improvement in corrosion resistance with laser surface treatment of austenitic stainless steel [30].…”
Section: Electrochemical Corrosion Testmentioning
confidence: 99%